Reversion and non-reversion mechanisms of resistance to PARP inhibitor or platinum chemotherapy in BRCA1/2-mutant metastatic breast cancer - Waks, A. G. (Ann Oncol, 2020)
BACKGROUND: Little is known about mechanisms of resistance to poly(adenosine diphosphate-ribose) polymerase inhibitors (PARPi) and platinum chemotherapy in patients with metastatic breast cancer and BRCA1/2 mutations. Further investigation of resistance in clinical cohorts may point to strategies to prevent or overcome treatment failure. PATIENTS AND METHODS: We obtained tumor biopsies from metastatic breast cancer patients with BRCA1/2 deficiency before and after acquired resistance to PARPi or platinum chemotherapy. Whole exome sequencing was carried out on each tumor, germline DNA, and circulating tumor DNA. Tumors underwent RNA sequencing, and immunohistochemical staining for RAD51 foci on tumor sections was carried out for functional assessment of intact homologous recombination (HR). RESULTS: Pre- and post-resistance tumor samples were sequenced from eight patients (four with BRCA1 and four with BRCA2 mutation; four treated with PARPi and four with platinum). Following disease progression on DNA-damaging therapy, four patients (50%) acquired at least one somatic reversion alteration likely to result in functional BRCA1/2 protein detected by tumor or circulating tumor DNA sequencing. Two patients with germline BRCA1 deficiency acquired genomic alterations anticipated to restore HR through increased DNA end resection: loss of TP53BP1 in one patient and amplification of MRE11A in another. RAD51 foci were acquired post-resistance in all patients with genomic reversion, consistent with reconstitution of HR. All patients whose tumors demonstrated RAD51 foci post-resistance were intrinsically resistant to subsequent lines of DNA-damaging therapy. CONCLUSIONS: Genomic reversion in BRCA1/2 was the most commonly observed mechanism of resistance, occurring in four of eight patients. Novel sequence alterations leading to increased DNA end resection were seen in two patients, and may be targetable for therapeutic benefit. The presence of RAD51 foci by immunohistochemistry was consistent with BRCA1/2 protein functional status from genomic data and predicted response to later DNA-damaging therapy, supporting RAD51 focus formation as a clinically useful biomarker.